2011
DOI: 10.3390/ijerph8072816
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term γ-Hydroxybutyric Acid (GHB) and Disulfiram Combination Therapy in GHB Treatment-Resistant Chronic Alcoholics

Abstract: Leading Italian studies support the use of γ-hydroxybutyric acid (GHB), not only in the treatment of the alcohol withdrawal syndrome, but also in maintaining alcohol abstinence. GHB gives a better result than naltrexone and disulfiram in maintaining abstinence, and it has a better effect on craving than placebo or disulfiram. The problem is that about 30–40% of alcoholics are non-responders to GHB therapy. In our clinical practice, we speculate that by combining disulfiram with GHB treatment we may be able to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In this regard, it is particularly interesting that γ-hydroxybutyric acid (GHB), which has been characterized as an agonist at GABA-B receptors (Andresen et al , 2011, Carai et al , 2008, Schep et al , 2012, Vienne et al , 2010), reduces alcohol consumption in animal models (Colombo et al , 2012), and is used to treat alcohol dependence and craving in Europe (Addolorato et al , 2011, Maremmani et al , 2011). Recently, GHB has been found to be a partial agonist at GABA-A receptors that contain α, β and δ (but not α, β and γ) subunits (Absalom et al , 2012).…”
Section: The Molecular Site Of Ethanol’s Action In the Cnsmentioning
confidence: 99%
“…In this regard, it is particularly interesting that γ-hydroxybutyric acid (GHB), which has been characterized as an agonist at GABA-B receptors (Andresen et al , 2011, Carai et al , 2008, Schep et al , 2012, Vienne et al , 2010), reduces alcohol consumption in animal models (Colombo et al , 2012), and is used to treat alcohol dependence and craving in Europe (Addolorato et al , 2011, Maremmani et al , 2011). Recently, GHB has been found to be a partial agonist at GABA-A receptors that contain α, β and δ (but not α, β and γ) subunits (Absalom et al , 2012).…”
Section: The Molecular Site Of Ethanol’s Action In the Cnsmentioning
confidence: 99%
“…In addition, a recent Cochrane meta‐analysis of 13 RCTs, confirming the favourable results of comparison with placebo, concluded that SO is more effective than NTX and DF in maintaining alcohol abstinence and reducing alcohol craving . Moreover, two studies have demonstrated that treatment with SO in combination with NTX or DF was significantly superior in maintaining complete abstinence from alcohol than monotherapy . SO, at the dosage of 50–100 mg/kg/day, is generally well tolerated, and the most common side effects are drowsiness, dizziness and asthenia, which do not require drug discontinuation, but disappear spontaneously.…”
Section: Abstinencementioning
confidence: 93%
“…However, 30-40% of patients do not respond to GHB treatment (75). For this reason, in one study GHB and disulfiram were used in combination, finding that the combination therapy increased the number of days staying in treatment and the number of days of abstinence compared to GHB therapy on its own (76). However, especially in patients with psychiatric comorbidities and other substance use disorders, sodium oxybate craving and sodium oxybate abuse were observed (77).…”
Section: Other Pharmacotherapies Approved In the Countries Of The Eurmentioning
confidence: 99%